La forja de una opinión pública Leer y escribir en Buenos Aires, 1800-1810 - Martínez Gramuglia, Pablo (Ariadna Ediciones, 2021)
The American events of the early nineteenth century, in addition to their strictly political and administrative aspects, also involved the installation of nascent modes of expression and meaning of the public word and writing. Those that developed in this sense in Buenos Aires at that time represent what, nuances more nuances less, also happened in the other urban centers of the region, rushing towards a wide panorama of changes in the forms and functions of discourse in its different arrays.